Twitter as political acclamation - Hegelich, Simon; Dhawan, Saurabh; Sarhan, Habiba (Frontiers in Political Science, 2023)
Acclamation as political form of communication has been used to understand political phenomena by a range of 20th century thinkers and recently has been used to analyze social media. However, if the notion of social media as acclamation is to be fruitful, it should be closely connected to inherent features of social media as technology and should be available to empirical analysis. To do so, this study follows a mixed-method approach. First, we offer a theoretical analysis of acclamation and how it links to each of the constituent parts of social media. Next, we build upon this theoretical analysis to study acclamation and social media as a matter of empirical data analysis to analyse the Tweets of the US-Presidents Obama, Trump and Biden. We apply regression models to measure the effects of acclamation. Our results show that acclamation is an essential feature of political communication but different for each President. This is in parts caused by the algorithms of Twitter which have different effects on the communication of the three Presidents. Our findings expand the idea of social media as acclamation and prove its relevance to the current political discourse.